Prevalence and molecular characterization of vancomycin-resistant enterococci isolated from poultry, raw vegetables and clinical sources - Ooi, Wai Ling (2003)
In this study, vancomycin-resistant Enterococcus (VRE) were isolated from 120, 60, 180, 450, 850, and 850 with chicken samples (CS), whole chicken (W), hospital clinical samples (HCS), environmental chicken faecal samples (CFS), ulam (U) and vegetables samples, respectively. All these samples were obtained mainly from wet markets and areas around Sri Serdang, Seri Kembangan and Kuala Lumpur. Vancomycin-resistant enterococci isolated from these samples were characterized phenotypically and genotypicall y. The prevalence of VRE isolated are as follow: HCS (14/180, 7.8%) with 1 isolate as E.faecalis (1114, 7.1 %) and 13 as E. faecium (13114, 92.9%); CFS (27/450, 6%) with 24 isolates as E. raffinosus (24/27, 88.9%) and 3 as E. faecium (3/27,11.1%);W(8/60, 13.3%) with 1 isolate as E. faecalis (118,12.5%), 2 as E. gallinarum (3/8, 37.5%), and 4 as E. faecium (4/8, 50. 0%); CS (1611 20,13 .3%) with 2 isolates identified as E. gallinarum (2116, 12.5%), 3 as E. faecalis (3/16,18.8%) and 11 as E. raffinosus (11116, 84.6%); U(8/850, 0.9%) with 3 isolates as E. faecium (3/8, 37.5%) and 5 as E. rafjinosus (5/8, 62.5%); V (8/850, 0.9%) with 5 as E. faecium (5/8, 62.5%) and 3 as E. gallinarum (3/8, 37.5%). The MAR index for VRE isolates examined ranged from 0.07-0.93 with E. rafjinosus having the highest ARI value. Among the 14 antibiotics tested, the highest prevalence of resistance was against kanamycin, streptomycin, erythromycin, bacitracin, tetracycline, and vancomycin (100%); cefuroxime and chloramphenicol (93%), penicillin G (89%), gentamicin (52%), while the lowest resistance was observed for ampicillin (40%), ceftriaxone (34%), rifampicin (10%) and teicoplanin (0%). The VRE isolates generated various plasmid profiles with sizes ranging from 1.7-35.8 MDa. Most isolates were found devoid of plasmid. The multiplex PCR (MPCR) displayed 3 identified isolates habouring the vanA gene (3.7%), whereas, in single PCR, 42 isolates harboured the vanA gene (51.85%). Both M-PCR and single PCR identified 1 isolate (V13) habouring vanB gene, whilst, 16 VRE isolates isolated from CFS, V and U samples were positive for vanC] gene. No vanC2,3, vanD, vanE and vanG genes were detected among the isolates. Three random primers, GEN 1-50-03 (5'-CTT GAG TGG A-3'), GEN 1-50-05 (5'-TCC TCAAGA C-3'), and GEN 1-50-08 (5'-GAG ATG ACG A-3') used in RAPD-PCR analysis produced bands with molecular size ranging from 0.25 kb to 3.0 kb.